Analysis of the “European Charter on General Principles for Protection of the Environment and Sustainable Development” The Council of Europe Document CO-DBP (2003)2 - Martin, Maria A; Martínez de Anguita, Pablo; Acosta, Miguel (Journal of agricultural & environmental ethics, 2013)
For almost 50 years, the Council of Europe through a series of documents has been helping to build up a set of rules, principles, and strategies related to culture, environment, ethics, and sustainable development. At the moment, one of the most important aims of the Council of Europe’s agenda deals with the elaboration of the General Principles for the Protection of the Environment and Sustainable Development, as raised in document CO-DBP (2003)2 related to the environmental subject. The intention of the Council of Europe is to encourage national authorities to implement these General Principles into their national environmental policies. These principles should have an important effect, especially in those countries which are new members of the European Union. The primary target of this paper is the study of these principles and the setting of their entailed implications in order to establish a relation between values and policy making. Quite often, the conclusions adopted by the agreements generated within the framework of the European Union are controversial. Therefore, a study aiming to lay the foundations of these principles will make the exchange of ideas easier, providing a wider and more detailed scope in the European environmental policy.